Case report: A Saprochaete clavata (Magnusiomyces clavatus) severe infection effectively treated with granulocyte transfusion in a young patient with myeloid sarcoma - Pasqualone, Gianmario; Buzzatti, Elisa; Palmieri, Raffaele; Savi, Arianna; Pascale, Maria Rosaria; Borsellino, Beatrice; Guarnera, Luca; Buccisano, Francesco; Voso, Maria Teresa; Maurillo, Luca; Sconocchia, Giuseppe; Venditti, Adriano; et al. (Frontiers in Oncology, 2022)
Myeloid sarcoma is a hematologic malignancy consisting of extramedullary tissue involvement by myeloid blasts, usually considered as acute myeloid leukemia and treated accordingly. Disease itself, togheter with chemotherapy and disease-associated factors may have an impact in increasing the risk of developing severe and frequently life-threatening infections. Herein, we describe the case of a patient with a right breast skin lesion, histologically diagnosed with as myeloid sarcoma, who developed a severe disseminated fungal infection by Saprochaeta clavata (Magnusiomyces clavatus), during the first consolidation course of chemotherapy. Despite maximum antifungal therapy, the infection progressed and fungus continued to be isolated until granulocyte transfusion therapy was initiated. Our experience suggests that patients with profound and long-lasting neutropenia could benefit from granulocyte transfusions as additional therapy in severe fungal infections resistant to broad spectrum antimicrobial therapy.